Advanced 3D Cell Culture Technologies and Formats - Cornelia Kasper; Dominik Egger (Bioengineering)
The Special Issue “Advanced 3D Cell Culture Technologies and Formats” presents a collection of original research and review articles that explore recent innovations in three-dimensional (3D) cell culture systems aimed at enhancing the physiological relevance and therapeutic utility of cells and cell-derived products and assays [...]